2015
DOI: 10.1017/s1049023x15004707
|View full text |Cite
|
Sign up to set email alerts
|

Intubation Efficiency and Perceived Ease of Use of Video Laryngoscopy vs Direct Laryngoscopy While Wearing HazMat PPE: A Preliminary High-fidelity Mannequin Study

Abstract: The time to successful ETI was not significantly different between VL and DL. Video laryngoscopy had a greater perceived ease of use, but DL was perceived to be more feasible for use in actual HazMat situations. These findings suggest that both DL and VL are reasonable modalities for use in HazMat situations, and the choice of modality could be based on the clinical situation and provider experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…In the present survey, we showed that the Airtraq is superior in terms of visualizing the glottis and the vocal cords. In a mannequin study involving post-graduate year emergency medicine residents, Aberle et al showed that video laryngoscope with GlideScope had a higher perceived ease of use, but that traditional direct laryngoscopy was perceived to be more feasible for use in CBRN conditions [ 26 ]. Similarly, our study does not show better evaluation for the insertion of the probe in oropharyngeal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…In the present survey, we showed that the Airtraq is superior in terms of visualizing the glottis and the vocal cords. In a mannequin study involving post-graduate year emergency medicine residents, Aberle et al showed that video laryngoscope with GlideScope had a higher perceived ease of use, but that traditional direct laryngoscopy was perceived to be more feasible for use in CBRN conditions [ 26 ]. Similarly, our study does not show better evaluation for the insertion of the probe in oropharyngeal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…A supraglottic airway can be a faster way to establish an airway while in PPE or during difficult intubations, but it should be replaced by an endotracheal tube when deemed safe [45]. There is no difference in intubation times when comparing direct laryngoscopy to video laryngoscopy while wearing PPE; both intubating techniques are reasonable choices [46,47]. The intubating instrument should be chosen based on provider preference, equipment availability, and the clinical picture.…”
Section: Airway Managementmentioning
confidence: 99%
“…Aberle et al [11] have compared DL and GL while wearing PPE, using mannequins as subjects, but concluded that there was no difference in the time required for endotracheal intubation or in the ease of use. Moreover, Shin et al [12] compared DL and the Pentax-Airwayscope (AWS, Pentax Corporation, Japan), which is a type of portable video laryngoscope, while wearing or not wearing PPE, and using mannequins as subjects.…”
Section: Case Reportmentioning
confidence: 99%